Knowledge, Attitude and Practice of Contraception among Postpartum Women Attending Kathmandu Medical College Teaching Hospital - Bajracharya, A. (Kathmandu University Medical Journal, 2017)
Background Failure to plan a pregnancy can adversely affect the health of the family as a whole. High parity is related to increased maternal, perinatal and infant deaths and is associated with nutritional problems of both mother and child. Hence, good knowledge, attitude and practice of family planning among women are important. This study is aimed to determine the knowledge, attitude and practice of contraception among the postpartum women attending Kathmandu Medical College Teaching Hospital. Objective To determine the knowledge, attitude and the practice of various contraceptive methods among the postpartum women. Method A cross-sectional observational study was conducted in the department of Obstetrics and Gynecology on 400 postpartum women (within 42 days of delivery) who delivered and came for follow-up in this institution. All the postnatal women were interviewed with pre-designed questionnaire and information on sociodemographic variable, awareness and knowledge of various contraceptive methods, previous and current use of family planning methods, source of information, utilization and reasons for use/non-use of family planning methods were obtained. Data collected were entered and analyzed using SPSS 20. The results were presented as percentages, means, tables and charts. Result Majority of the participants 363 (90.8%) were aware of contraceptive usage. Amongst 60.5% of women who had previously used contraception, OCPs were the commonest one. Maximum number of participants (60.35%) had used modern contraceptives in the past. The most common source of information on contraception was media (55.7%). The reason of using contraception was spacing between the subsequent pregnancies, while the most common reason of discontinuation or not willing to use family planning methods was husband being abroad, fear of side effects and not knowing which contraceptives to use. Conclusion The contraceptive awareness and knowledge among the postpartum women was high but their usage was low. Hence, efforts should be made to educate the public about safety and convenience of modern methods of contraceptives. Health care personnels should also counsel the clients for adopting the contraceptives according to their need.